2003
DOI: 10.1051/0004-6361:20031161
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic activity of six young solar analogues II. Surface Differential Rotation from long-term photometry

Abstract: Abstract. The present paper is the second of a series dedicated to the study of the magnetic activity in a selected sample of young solar analogues. The sample includes five single G0-G5V stars with ages between 130 Myr and 700 Myr: EK Dra, π 1 UMa, HN Peg, k 1 Cet and BE Cet. In this study we also include the Pleiades-age ( 130 Myr) K0V star DX Leo. Our analysis is based on high precision photometric observations carried out as part of The Sun in Time project, aimed at a multiwavelength study of stars with so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
127
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 111 publications
(145 citation statements)
references
References 37 publications
(30 reference statements)
17
127
1
Order By: Relevance
“…The first period is also found to be similar to the latitudinal spot migration period derived from SDR analysis, which could be similar to the 11 yr cycle of the solar butterfly diagram. This type of activity cycle was also observed in similar fast-rotating stars such as AB Dor (Collier Cameron & Donati, 2002; and LQ Hya (Messina & Guinan, 2003). In the SDR analysis, the decrease in photometric periods within most of the cycles is reminiscent of the sunspot cyclic behaviour, where the latitude of spot-forming region moves towards the equator, i.e., toward progressively faster rotating latitudes along an activity cycle, and spot-groups were present within ±45 • latitude of LO Peg.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The first period is also found to be similar to the latitudinal spot migration period derived from SDR analysis, which could be similar to the 11 yr cycle of the solar butterfly diagram. This type of activity cycle was also observed in similar fast-rotating stars such as AB Dor (Collier Cameron & Donati, 2002; and LQ Hya (Messina & Guinan, 2003). In the SDR analysis, the decrease in photometric periods within most of the cycles is reminiscent of the sunspot cyclic behaviour, where the latitude of spot-forming region moves towards the equator, i.e., toward progressively faster rotating latitudes along an activity cycle, and spot-groups were present within ±45 • latitude of LO Peg.…”
Section: Discussionsupporting
confidence: 72%
“…It is interesting to note that the slope of the rotational period on LO Peg varies and therefore SDR amplitude ∆P (= Pmax − Pmin) changes from cycle to cycle. Similar behaviour was also observed in AB Dor (Collier Cameron & Donati, 2002), BE Cet, DX Leo, and LQ Hya (Messina & Guinan, 2003). This resembles either a wave of excess rotation on a time-scale of the order of decades, or a variation of the width of the latitude band in which spots occur.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…They found that the fastest rotating stars tended to display longer cycles, with the range of the observed cycle periods apparently converging from a large dispersion at ages of ≈ 100 − 200 Myr toward the solar cycle period at the age of the Sun. Messina & Guinan (2003) investigated the correlation between the period of the rotational modulation and the phase of the cycle in the above sample of stars finding a clearly significant correlation in two of them, and a less significant correlation in the other four. Both solar-like and anti-solar behaviours were observed, as in the case of the chromospheric cycles of the H&K project sample.…”
Section: Stellar Cycles From Photospheric Proxiesmentioning
confidence: 99%
“…Assuming that α 0 = Ωl, Ω ∝ Ω, and η t = l 2 /τ c , where l is the mixing length at the base of the stellar convective envelope, we find D ∝ Ro −2 . Therefore, the Rossby number is a measure of the dynamo number which can be derived by combining observations of the stellar rotational modulation with a model of its internal structure (see, e.g., Messina & Guinan 2003).…”
Section: Stellar Cycles From Photospheric Proxiesmentioning
confidence: 99%